Effectiveness of Annona muricata Leaf Extract as a Biopesticide Against Strepsicrates sp. in Eucalyptus pellita Seedlings - Zahra’ Syafi’ah; Muhammad Mardhiansyah; Pebriandi Pebriandi (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: Industrial forest plantations, particularly Eucalyptus pellita, are widely cultivated for pulp and paper production. However, nurseries of E. pellita, including those in the R&D facilities of PT Arara Abadi, are frequently infested by pests such as Strepsicrates sp. Synthetic pesticides are commonly applied to manage these infestations, although their use may pose risks to the environment. As an alternative, botanical pesticides derived from Annona muricata leaf extract have gained attention. Therefore, this study aimed to evaluate the effectiveness of A. muricata leaf extract in controlling Strepsicrates sp. and to determine its optimal concentration for application in E. pellita nurseries. Methodology: The experiment employed a completely randomized design (CRD) consisting of four treatments with five replicates. Data were analyzed using Duncan’s New Multiple Range Test (DNMRT) at a 5% significance level. The treatments consisted of concentrations of 10 g/L, 20 g/L, 30 g/L, and 40 g/L. Observed parameters included room temperature, relative humidity, time to initial mortality, time to 50% mortality, daily mortality rate, and total mortality. Findings: A. muricata leaf extract was effective in controlling Strepsicrates sp. on E. pellita. The results indicated that the optimal concentration was 40 g/L, resulting in the shortest initial mortality time of 5.2 hours, a median lethal time (LT₅₀) of 22.58 hours, and  a total mortality rate of 100%. Contribution: The findings of this study indicate that A. muricata leaf extract at a concentration of 40 g/L has strong potential for application as an environmentally friendly, effective, and sustainable botanical pesticide, supporting integrated pest management in E. pellita nurseries and reducing reliance on synthetic chemicals